PENDIDIKAN KARAKTER BERBASIS PESANTREN - Saiful Saiful (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2019)
Abstract: The superiority of character education in Islamic boarding school can be seen from the education system that is developed consistently in forming a moral and responsible Muslim personality. Education in Islamic boarding school does not have a complete learning trap, but produces graduates who have lofty character, otherwise in public education institution the education system has a clear learning trap, but it does not produce graduates who have noble character. The interesting side of education in Islamic boarding schools is that between teacher and student there is a feeling of respect and the student obedient to the teacher. The respect and obedience of the students to the teacher is uninterrupted and applies lifetime. Character education taught in Islamic boarding school includes respecting(ta’ẓīm)to parents, scholars, kissing the hands of the teacher, good example, manners, simplicity, honesty, trustworthiness, responsibility and independence. The methods of character education in Islamic boarding School, there are: Exemplary methods, taking lessons(ibrah), advice methods(mauī’ẓah), disciplinary methods, targhīb wa tahzīb method, and independence methods.Key Word: Education character and Pesantren